Suurkeittiöt elintarvikealan pienyritysten markkinointikanavana - Aro, Johanna (Maatalouden taloudellinen tutkimuslaitos, 1998)
Suurkeittiöt ovat potentiaalinen, mutta suhteellisen vähän käytetty markkinointikanava elintarvikealan pienyrityksille. Suurkeittiöiden ja pienyritysten välisen kaupankäynnin erityispiirteenä voidaan pitää sitä, että suurkeittiöt hankkivat tyypillisesti tuotteet suoraan pienyrityksiltä. Vuorovaikutussuhteilla on ratkaistava merkitys, vaikka sekä pienyrittäjät että suurkeittiöostajat painottavat tuote- ja palvelutekijöitä usein enemmän kuin vuorovaikutussuhteita. Suurkeittiömarkkinoilla on paljon kilpailua, ja tukkuportaan vahva asema vaikeuttaa elintarvikealan pienyritysten ja suurkeittiöiden välisen yhteistyön kehittämistä. Pienyritysten vahvuuksia ovat nopea reagointi- ja sopeutumiskyky. Pienyrityksen näkökulmasta suurkeittiöiden hyvä palvelu edellyttää markkinointikanavaan keskittymistä ja yrittäjän omaa aktiivisuutta. Paras keino hinnan merkityksen vähentämiseen ja neuvotteluvoiman parantamiseen on vuorovaikutussuhteiden korostaminen ja tuotteiden erilaistaminen niin sanotuista massatuotteista poikkeaviksi. Suurkeittiökanavaan pääsy avaa pienyrityksille mahdollisuuksia pitkiin yhteistyösuhteisiin, mutta on tärkeää muistaa, että suhteiden menestyksekäs ylläpito vaatii usein vähintään yhtä paljon työtä kuin suhteiden luominen.

The aim of this study was to examine co-operation between small food processing firms and restaurants, catering firms, and institutional food service units. The theoretical part of the study descriped marketing channels decisions of the small firms, buying activities at restaurants, catering firms, and institutional food service units and theories of relationship marketing. The aim of the empirical part of the study was to examine different product and service factors, and especially relationship factors, that contribute at transaction process. The empirical part was conducted using in-depth interviews. The data consist of the results of interviews with 11 entrepreuneurs of small food producing firms and 15 buyers at restaurants, catering firms, and institutional food service units in the Southern Finland. According to the results, those small firms that were focused on service of restaurants, catering firms, and institutional units recognised their clientsŽ different needs and expectations better than those firms who werenŽt focused in their action. Focused firms had successed to create long and active contacts with their clients. Small firms stressed the meaning of relationships and interaction at the situation, where the buyer at the role of decision maker was also the user of the food product or service. These kinds of relationships were most common at private restaurants, whereas buying activities at chain restaurants resembled buying activities at institutional food service units. A particular feature at the transaction process was that restaurants, catering firms, and institutional food service units typically buy products and services directly from small firms. Relationships had a crucial purpose, even thought according to this study both small firms and buyers at restaurants and institutional food service units usually pointed out product and service factors more than relationship factors. Buyers at the restaurants, catering firms, and institutional food service units emphasised differently the value gained from maintaining the relationships. According to the buyers in private restaurants, the additional value at the relationships was tightly bonded to interaction between buyers and sellers. At the chain restaurants the possibilities to mutual economical benefits was emphasised most. At the institutional food service units, food preparing staff didnŽt stress the meaning of relationships, but decision makers felt that the additional value of relationships was bonded to trust achieved during long time period. The trust was crucial factor if there were many equal deliverers. At the future, restaurants, catering firms, and institutional food service units are to be considered as a potential marketing channel for small food processing firms. Small firms can find the best opportunities among the private restaurants, whereas at the chain restaurants and institutional food service units the basic knowledge about buying organisationŽs supply actions improve small firmsŽ opportunities to increase the publicity of their products and services.
Keywords: Ma; markkinointikanava; suurkeittiöt; pienyritykset; markkinointi; small food processing firms; restaurants; catering firms; institutional food service units; relationship marketing